Complementary Therapy for Cancer Survivors: Integrative Nursing Care - Kazuko Onishi (Elsevier, 2016)
Objective: The number of cancer patients who survive more than 5 years after the completion of their initial treatment is increasing. Oncology nurses must consider the needs of long-term cancer survivors in addition to those of cancer patients undergoing treatment because cancer survivors experience anxiety over several issues, including the risk of recurrence and progression of cancer status and symptom management. Methods: We tried to examine the effect of complementary therapy (CT) to reduce anxiety. The experimental study compared an intervention group (5 males and 68 females) that underwent four CTs and a control group (5 males and 56 females) that received no intervention. The intervention group practiced the CTs in their home for 20 min/day, 2 days/week, for 8 weeks, for a total of 16 times, whereas the control group performed their usual routines. Stress response scale-18 (SRS-18) scores consisting of three subscales (depression-anxiety, temper-anger, and lethargy) were compared between the groups and across time within each group. Results: The intervention group reduced depression and anxiety significantly than the control group. Furthermore, the intervention group expressed the following positive feedback: "being able to relax," "being distracted from their worries and anxieties," "being able to sleep," "feeling more in-touch with reality," and "wanting to continue the practice." Conclusions: The study might accurately reflect the perspectives of women with cancer because the majority of the patients were women. Meanwhile, the result suggests that CTs might be useful for long-term cancer survivors who experience anxiety that influence their quality of life.